A study on clinical profile, management and outcome in pediatric patients admitted with scorpion envenomation - Umapathi, Kiruthika; Boopalan, P.; Maheshkumar, V. P.; Ramamoorthy, R. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Scorpion envenomation is a common medical emergency. The main aim is to study clinical profile, management and outcome. Methods: Prospective observational study of Scorpion envenomation cases for six months. case sheets were analysed for clinical profile, symptoms, complications, management and outcome. Results: During the study period first 50 cases were admitted and treated for the following results 66% were males and 34% were females, 46% were upper extremity and 54% were lower extremity. common clinical symptoms are pain at site, autonomic storm, palpitation, headaches, abdominal pain, altered sensorium, vomiting. 40% of patients received prazosin with 1-2 hrs. the major complications were myocarditis, encephalopathy, Peripheral circulatory failure & congestive cardiac failure. There was no mortality in this study. Conclusions: The study finding shows that early and effective use of prazosin treatment showed good outcome in patients. Less complications were seen in patients those who received the first aid. This study concludes that majority of patient were exposed to complication due to shortfall in education, awareness and pre-hospitalization. We, as a clinical pharmacist, tried to create awareness and provide education to health care workers in all primary health care center through distributing pamphlets to general public in and around hospital.